Functional and structural asymmetry in primary motor cortex in Asperger syndrome: a navigated TMS and imaging study - Säisänen, Laura (Brain Topogr, 2019)
Motor functions are frequently impaired in Asperger syndrome (AS). In this study, we examined the motor cortex structure and function using navigated transcranial magnetic stimulation (nTMS) and voxel-based morphometry (VBM) and correlated the results with the box and block test (BBT) of manual dexterity and physical activity in eight boys with AS, aged 8–11 years, and their matched controls. With nTMS, we found less focused cortical representation areas of distinct hand muscles in AS. There was hemispheric asymmetry in the motor maps, silent period duration and active MEP latency in the AS group, but not in controls. Exploratory VBM analysis revealed less gray matter in the left postcentral gyrus, especially in the face area, and less white matter in the precentral area in AS as compared to controls. On the contrary, in the right leg area, subjects with AS displayed an increased density of gray matter. The structural findings of the left hemisphere correlated negatively with BBT score in controls, whereas the structure of the right hemisphere in the AS group correlated positively with motor function as assessed by BBT. These preliminary functional (neurophysiological and behavioral) findings are indicative of asymmetry, and co-existing structural alterations may reflect the motor impairments causing the deteriorations in manual dexterity and other motor functions commonly encountered in children with AS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10548-019-00704-0) contains supplementary material, which is available to authorized users.